Taxation of Digital Platforms - Marko Köthenbürger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Tech giants such as Google and Facebook generate significant amounts of advertising income, which is mainly reported in low-tax countries. This has created a policy discussion of how to re-align the location of value creation and taxation. The success of the business model of these digital platforms relies on the existence of indirect network effects, which are the prime reason why platforms exist and generate advertising income. To account for these effects, conventional tax policy needs to be adjusted. This includes an adjusted concept of nexus that should rely on the location of users, which generate the relevant indirect network effects. The recent EU proposal of a digital service tax goes in this direction and constitutes a policy option for other countries.
Keywords: D43; H21; H22; L13; 330; Digitale Medien; Internetportal; Werbung; Einnahmen; Steuer; Theorie